2021
DOI: 10.1111/edt.12662
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pediatric maxillofacial fractures in Kuwait: A single‐center retrospective study

Abstract: Background Pediatric maxillofacial fractures always present a challenge due to the unique nature of the facial skeleton anatomy and development. The aim of this study was to investigate the incidence, etiology, site of fracture, and management modalities of pediatric maxillofacial fractures in Kuwait. Methods A retrospective cross‐sectional study was conducted. The records of all pediatric patients who were diagnosed with maxillofacial fractures and admitted to one of the major hospitals in Kuwait between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
(28 reference statements)
3
8
0
Order By: Relevance
“…Possibly, it can compensate for the deficiency of MPR, the three-dimensional display of the anatomical structure, and fracture images of the maxillofacial region and thus providing a more intuitive and three-dimensional understanding of the relationship between the broken end and the spatial structure of the surrounding tissues [ 18 , 19 ]. Similarly, Alessa concluded that the detection rate of MPR plus VR was superior to that of axial CT (99.5% (209/210) vs 88.1% (185/210)), confirming that CT scan 3D reconstruction technology has a reliable value [ 20 ]. In addition, with the results of surgical anatomy as the gold standard, the sensitivity of MRP and VR for the diagnosis of maxillofacial fractures was 90.06% (163/170) and 95.56% (174/177), respectively, with no significant difference.…”
Section: Discussionmentioning
confidence: 98%
“…Possibly, it can compensate for the deficiency of MPR, the three-dimensional display of the anatomical structure, and fracture images of the maxillofacial region and thus providing a more intuitive and three-dimensional understanding of the relationship between the broken end and the spatial structure of the surrounding tissues [ 18 , 19 ]. Similarly, Alessa concluded that the detection rate of MPR plus VR was superior to that of axial CT (99.5% (209/210) vs 88.1% (185/210)), confirming that CT scan 3D reconstruction technology has a reliable value [ 20 ]. In addition, with the results of surgical anatomy as the gold standard, the sensitivity of MRP and VR for the diagnosis of maxillofacial fractures was 90.06% (163/170) and 95.56% (174/177), respectively, with no significant difference.…”
Section: Discussionmentioning
confidence: 98%
“…According to several authors, RTA is the main cause of oro‐maxillofacial fractures. 18 , 23 , 27 , 35 Patients suffering trauma from RTA had the highest median age among the causes of trauma, with 68% of all RTA‐related fractures in the adolescent group (Table 1 ). In addition, RTA was the main cause of maxillofacial paediatric fractures in all African and Asian centres, ranging from 42% to 69% (Table 2 ), in agreement with several studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, characteristics of facial injuries in children and adolescents also vary among countries due to demographic, socioeconomic and environmental differences. Articles on the epidemiology of maxillofacial fractures in children and adolescents, which have often been monocentric and retrospective, have reported road traffic accidents (RTAs) as the most common cause in Africa, 11–13 Oceania 14,15 and America, 16–19 while falls were the most common in Europe 6,20,21 and Asia 22–25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Midfacial fractures account for 45.4% to 79.1% of all facial fractures and can seriously affect patient appearance and function [ 1 , 2 , 3 , 4 , 5 ]. The midfacial region is defined based on the resulting AO CMF classification system within anatomical regions: zygoma, upper central midface, intermediate central midface, lower central midface, frontal, parietal, sphenoidal, and temporal [ 6 ].…”
Section: Introductionmentioning
confidence: 99%